Ação do extrato de própolis na Leishmaniose - Oda, Julie Massayo Maeda; Fujita, Thiago Cezar; Pitz, Amanda de Fáveri; Amarante, Marla Karine; Felipe, Ionice; Saridakis, Halha Ostrensky; Sforcin, José Maurício [UNESP]; Watanabe, Maria Angélica Ehara; Costa, Ivete Conchon (Universidade Estadual de Londrina, 2011)
Leishmaniasis is a public health problem causing morbidity and mortality in over 80 countries and features a parasitic disease with several manifestations. In the New World occur Visceral Leishmaniasis (VL) and American Cutaneous Leishmaniasis (ACL). The ACL is considered a disease polymorphic of skin and mucous membranes, grouped in different clinical forms: cutaneous leishmaniasis in the skin and mucosa and diffuse cutaneous, and the evolution of this disease is closely related to the mechanisms of escape of the protozoan Leishmania from the immune response, allowing the development of the disease and consequently the onset of clinical manifestations known. The World Health Organization recommends the pentavalent antimony as the first choice drugs. However, they usually give unsatisfactory results, requiring the development of new and affordable drugs for its treatment. It has been investigated that use of propolis it is related to exhibit several biological activities such as antibacterial, antifungal, anti-ulcer agents, antiviral, anti-protozoan, anti-inflammatory, hepatoprotective, antioxidant, antitumor, among others. Recent studies have shown that green propolis active macrophages and stimulates lymphocytes B to produce antibodies. It was also reported that propolis shows a potential antileishmanial activity by reducing the diameter of the lesions, avoiding complications of the lesions by bacteria or by improving the immune response against the Leishmania through macrophages activation. The aim of this work was related the main activities leishmanicida using propolis, by searched the electronic literature PubMed and Scielo during the year 2009.

A leishmaniose causa mortalidade e morbidade em mais de 80 países e caracteriza-se como uma doença parasitária com diversas manifestações, por isso constitui um sério problema de saúde pública. No Novo Mundo ocorre a Leishmaniose Visceral (LV) e Leishmaniose Tegumentar Americana (LTA). A LTA é considerada uma enfermidade polimórfica, espectral da pele e das mucosas, agrupada em diferentes formas clínicas: a leishmaniose cutânea, a cutaneomucosa e a cutânea difusa. A Organização Mundial da Saúde recomenda os antimoniais pentavalentes como drogas de primeira escolha no tratamento da leishmaniose. Entretanto, devido aos efeitos indesejados dessas drogas, tem sido proposto o estudo para o desenvolvimento de novos fármacos para seu tratamento. Assim, tem-se investigado o uso da própolis, visto que está relacionada a muitas atividades biológicas, como antibacteriana, antifúngica, antiulcerativa, antiviral, antiprotozoária, antiinflamatória, hepatoprotetora, antioxidante, antitumoral, entre outras. Estudos recentes mostraram que a própolis verde ativa macrófagos e estimula os linfócitos B a produzirem anticorpos. A própolis tem demonstrado potencial atividade leishmanicida, por diminuir o diâmetro das lesões, causar alterações morfológicas nas formas promastigotas ou ainda por melhorar a resposta imunológica frente às Leishmanias, ativando macrófagos.Portanto, o objetivo deste trabalho foi relatar as principais atividades leishmanicidas da própolis, por meio de pesquisa bibliográfica eletrônica no PubMed e Scielo durante o ano de 2009.
Keywords: PRÓPOLIS; Leishmania